Transcriptional stimulation of rate-limiting components of the autophagic pathway improves plant fitness. (20th January 2018) - Minina, Elena A; Moschou, Panagiotis N; Vetukuri, Ramesh R; Sanchez-Vera, Victoria; Cardoso, Catarina; Liu, Qinsong; Elander, Pernilla H; Dalman, Kerstin; Beganovic, Mirela; Lindberg Yilmaz, Jenny; Marmon, Sofia; Shabala, Lana; et al.
Abstract : Autophagy-related proteins Atg5 and Atg7 are rate-limiting components of autophagic flux in Arabidopsis. Overexpression of ATG5 or ATG7 genes stimulates Atg8 lipidation, autophagosome formation, and autophagic flux, leading to improved plant fitness. Abstract: Autophagy is a major catabolic process whereby autophagosomes deliver cytoplasmic content to the lytic compartment for recycling. Autophagosome formation requires two ubiquitin-like systems conjugating Atg12 with Atg5, and Atg8 with lipid phosphatidylethanolamine (PE), respectively. Genetic suppression of these systems causes autophagy-deficient phenotypes with reduced fitness and longevity. We show that Atg5 and the E1-like enzyme, Atg7, are rate-limiting components of Atg8–PE conjugation in Arabidopsis. Overexpression of ATG5 or ATG7 stimulates Atg8 lipidation, autophagosome formation, and autophagic flux. It also induces transcriptional changes opposite to those observed in atg5 and atg7 mutants, favoring stress resistance and growth. As a result, ATG5 - or ATG7 -overexpressing plants exhibit increased resistance to necrotrophic pathogens and oxidative stress, delayed aging and enhanced growth, seed set, and seed oil content. This work provides an experimental paradigm and mechanistic insight into genetic stimulation of autophagy in planta and shows its efficiency for improving plant productivity.